Lysophosphatidylinositol-glucagon like peptide 1 crosstalk in metabolic diseases - Paternoster, Silvano (Curtin University, 2020)
This PhD thesis discusses the study of a novel class of drugs for the treatment of metabolic diseases. We have characterized the pharmacology and biology of the lipid Oleoyl-lysophosphatidylinositol (Oleoyl-LPI), and we show that some synthetic molecules mimicking its structure, are efficient glucagon-like peptide-1 (GLP-1) secreting drugs in vitro and in vivo in diabetic mice. We have also dissected the pharmacology of Cannabis-derived drugs and demonstrated that they can also modulate GLP-1 secretion.